(Tb3+, Eu3+)-Codoped Ga2O3 Phosphors: Synthesis and Photoluminescence Properties. (12th March 2016) - Sawada, Kenji; Nakamura, Toshihiro; Adachi, Sadao
Abstract : (Tb 3+, Eu 3+ )-codoped Ga2 O3 crystallites, together with Tb 3+ /Eu 3+ singly doped crystallites, were synthesized by metal-organic decomposition (MOD) and their material properties were studied in detail. The X-ray diffraction analysis indicated that only β -phase Ga2 O3 can be synthesized by the MOD and subsequent calcination at T c ≥ 700°C. Above ∼900°C, calcination treatment greatly reduced the Tb 3+ green and Eu 3+ red emission intensities. Therefore, the phosphor crystallites were mainly calcined at 800°C. The phosphor properties were examined using photoluminescence (PL) analysis, PL excitation spectroscopy, and PL decay measurement. The Tb 3+ and Eu 3+ emission intensities in the Ga2 O3 :Tb 3+, Eu 3+ phosphors by excitation at λ ex = 266 nm showed remarkable concentration quenching at ≥0.03 mol% (Tb 3+ ) and ≥0.1 mol% (Eu 3+ ), whereas those in the Tb 3+ /Eu 3+ singly doped samples showed concentration quenching at ≥0.1 mol%. The concentration quenching in the (Tb 3+, Eu 3+ )-codoped samples was confirmed by the PL decay measurements. The temperature dependences of the Tb 3+ and Eu 3+ emission intensities in the singly doped and codoped samples were measured at T = 20–450 K in increments of 10 K and analyzed by a simplified thermal quenching model. Discussion was made on the possibility of resonant energy transfer between Tb 3+ and Eu 3+ in the β -Ga2 O3 host.